2016
DOI: 10.18203/2320-6012.ijrms20161251
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors associated with development of ventilator-associated pneumonia from a tertiary care center of northern India

Abstract: Background:The incidence of VAP varies among different studies, depending on the definition, the type of hospital or ICU, the population studied, and the level of antibiotic exposure. This study was planned to ascertain and analyse the incidence and risk factors associated with development of ventilator-associated pneumonia from a tertiary care center. Methods: In this retrospective study, all the adult patients on mechanical ventilation (MV) for more than 48 hours in the Medicine Intensive Care Unit (MICU) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…17 Another study from northern India observed that the 2 most common organism isolated were Pseudomonas aeruginosa and Methicillin-resistant Staphylococcus aureus (MRSA). 4 Considerable controversy still surrounds treatment (monotherapy or combination) for patients with VAP, which depends on organisms recovered. The primary reasons for combination therapy are to prevent the development of resistance, improve outcomes, provide synergy, and provide sufficient antibiotic coverage should the pathogen be resistant to the agent that would have been chosen as single therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Another study from northern India observed that the 2 most common organism isolated were Pseudomonas aeruginosa and Methicillin-resistant Staphylococcus aureus (MRSA). 4 Considerable controversy still surrounds treatment (monotherapy or combination) for patients with VAP, which depends on organisms recovered. The primary reasons for combination therapy are to prevent the development of resistance, improve outcomes, provide synergy, and provide sufficient antibiotic coverage should the pathogen be resistant to the agent that would have been chosen as single therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of VAP varies among different studies, depending on the definition, the type of hospital or ICU, the population studied, and the level of antibiotic exposure. 4 Knowledge of the incidence of VAP and their associated risk factors are imperative for development and use of more effective preventive measures. While critically ill patients experience a life-threatening illness, they commonly contract VAP.…”
mentioning
confidence: 99%
“…Incidence of VAP Organism wise distribution of VAPMathai et al, (2016) 21 and Ranjan et al, (2014)22 with Acinetobacterspsas the most common organism isolated. In contrast Deshmukh et al, 23 and Husain Shabbir Ali et al, (2016)24 reported Pseudomonas aeruginosa as the most common organism.In our study mortality was 48.38% and it is consistent with the recent reports from Dube et al, Maqbool et al, Ranjan et al, Goel et al, (2012) 25 and Gupta et al, (2011) 26 . Higher mortality was reported by Gupta et al, as 78.94%.…”
mentioning
confidence: 92%
“…2 The incidence of VAP varies among different studies, depending on the definition, the type of hospital or ICU, the population studied, and the level of antibiotic exposure. 3 The causative…”
Section: Introductionmentioning
confidence: 99%